Developing Ethnomathematics-Based Learning Media on Fractions - Karmila Ayu; Azmidar Azmidar (Universitas Mercu Buana Yogyakarta, 2026)
Using ethnomathematics method, this study attempts to create and assess the quality of learning materials about fractions, especially equivalent fractions, related to local culture. The five steps of ADDIE development modelanalysis, design, development, implementation, and evaluation—are used in this study along with Research and Development (R&D) techniques. As a contextual method for learning equivalent fractions, fraction board media representing the shape of traditional Bugis cakes katirisala (rectangle), sikaporo (hexagon), and cucuru' bayao (circle) are created. With a percentage of 83.33% from material experts and 96.66% from media experts, the results of expert validation indicate that the developed media has a high level of validity and is included in the